2006
DOI: 10.1001/archpedi.160.11.1145
|View full text |Cite
|
Sign up to set email alerts
|

The Interpreter as Cultural Educator of Residents

Abstract: Objective: To determine whether augmentation of the Spanish interpreter's role to include cultural education of residents can improve the satisfaction of Latino patients. Design:We assessed parent satisfaction during 4 sequential 2-month periods between June 1, 2004, and February 11, 2005, using different interpretation methods: telephone interpretation (n = 91 patient encounters), trained in-person interpretation (n = 49), in-person interpretation with cultural education of residents (n=65), and postprogram t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…29 Previous studies have shown LEP families have increased satisfaction with care when receiving information by using trained, in-person interpreters. 28,3033 A recent study found only 68.8% of hospitals in the United States offered language services, including only 74.7% of hospitals characterized as having a high level of need for language services. 34 The cost of hiring interpreters may be considered prohibitive by some health care organizations; however, studies indicate that the estimated cost of providing interpreter services is relatively modest compared with the overall cost of health care and potential benefits, ranging from $4 to $279 per person per year.…”
Section: Discussionmentioning
confidence: 99%
“…29 Previous studies have shown LEP families have increased satisfaction with care when receiving information by using trained, in-person interpreters. 28,3033 A recent study found only 68.8% of hospitals in the United States offered language services, including only 74.7% of hospitals characterized as having a high level of need for language services. 34 The cost of hiring interpreters may be considered prohibitive by some health care organizations; however, studies indicate that the estimated cost of providing interpreter services is relatively modest compared with the overall cost of health care and potential benefits, ranging from $4 to $279 per person per year.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of family members in decision-making, especially husbands within the traditional African cultural ethos. All of these can serve as barriers to the appropriate practice of informed consent in developing country settings [34,74]. To further improve understanding and comprehension during the informed consent process, the US National Bioethics Advisory Commission (NBAC) has suggested that community participation is acceptable, which may include providing written information sheets for discussions with family members and holding community meetings, but cautions that family permission should not replace the requirement for individual informed consent [75,76].…”
Section: Discussionmentioning
confidence: 99%
“…Results from the Chen study show that properly designed educational programs for clinicians that increase cultural competency can also increase patient satisfaction with healthcare encounters. 38 …”
Section: Discussionmentioning
confidence: 99%
“…While language barriers have been shown to have an adverse impact on health care outcomes (e.g., utilization, status, receipt of preventive services), we did not find this in our study. 38, 49 However, Chen and colleagues found that Latinos who did not speak English at home were less likely to receive health care services regardless as to whether or not they were comfortable speaking English. 49 Assessing English language fluency with more extensive measures and also the language used when talking to providers will be important to consider in future investigations.…”
Section: Discussionmentioning
confidence: 99%